Karl Marx after New Institutional Economics - Pagano, Ugo (2006)
In this paper, we consider the two main causation mechanisms characterizing Marxian theory: the one running from productive forces to relations of production (Marx I) and the other moving in the opposite direction (Marx II). We argue that Marx did not achieve a satisfactory integration of the two mechanisms and that he failed to point out how multiple technological institutionalpaths may stem from the cumulative interactions between relations of production and productive forces. In spite of many important analytical insights, NIE has exacerbated the primacy of technology and productive forces, which characterized «Marx I». After NIE, the analysis of thecomplex relations between «Marx I» and «Marx II» can still help to extend the scope of institutional theory and, in particular, its application to the comparative analysis of models of capitalism coexisting in the global economy.